The impact of spinal cord injury on South African youth - E. Njoki; J. Frantz; R. Mpofu (AOSIS, 2007)
Approximately 500 South Africans, mainly young people, sustain a spinal cord injury every year leading to severe lifetime physical disabilities. With advances in medicine and assistive technology, these young people are able to reach adulthood. The physical, social and  emotional adjustments, which determine the eventual successful outcome following injury, vary considerably from person to person. Some make satisfactory adjustments whereas others remain chronically distressed. This study aimed to determine the impact of SCI on youth in community settings after discharge from rehabilitation.  A qualitative approach, that utilised face-to-face interviews and focus group methods of data collection, was used. Data were drawn from ten participants selected at Conradie Spinal Rehabilitation Unit, using purposive sampling. Audiotape recorded interviews were transcribed verbatim. Strong themes that ran through the data were identified. The results of the study revealed that spinal cord injury impacts on more than just the physical capabilities of an individual. Participants identified issues such as social identity, intrapersonal and interpersonal factors, social support and employment opportunities as having a major impact on their lives once back in the community.  It is  recommended that rehabilitation professionals include issues such as identity and psychosocial adjustment into their health promotion interventions.